Crossing Borders and Shifting Boundaries
VII, 305 p.
Keywords: The two volumes Gender and Migration: crossing borders and shifting boundaries offer an interdisciplinary perspective on women and men on the move today, exploring the diversification of migratory patterns and its implication in different parts of the world. It reflects the vibrant scholarly debates as well as unique learning and teaching experiences of the Project Area Migration, the International Women's University. While pointing to historical continuities, it is shown how contemporary ways of bridging time and space are shaped by the new opportunities - or lack of them - related to the process of globalization. This shaping is gendered. Gendering migration paves the way for further intersectional analysis. Vol. I critically examinesmobility, globalization and migration policy from a gender perspective. It includes case studies on internal and international migratory processes inand from Latin America, Europe, Africa, Asia and North America. Furthermore it makes an important contribution to the issue of agency and empowerment emerging from migrant women's experience. .